2019
DOI: 10.1101/834325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural similarities between some common fluorophores used in biology and marketed drugs, endogenous metabolites, and natural products

Abstract: St r uct ur al si m i l ar i t i es bet w een som e com m on f l uor oph or es used i n bi ol ogy an d m ar k et ed dr u gs, en dogen ou s m et abol i t es, an d n at u r al pr odu ct s St ev e O'Hagan 1,2 , Dou gl as B. Kel l 1,2,3,4 * 1 School of Chem istr y, 2 M anchester Insti tute of Bi otechnology, The Uni ver si ty of M anchester , 131 Pr incess St, M anchester M1 7DN, UK 3 (and pr esent addr ess): Depar tm ent of Biochem istr y, Institute of Integr ative Biology, Biosciences Building, Univer sity of L… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…(B) UMAP [24] representation of the chemical space of ∼6 M 'druglike' molecules from ZINC. This is largely seen to contain the ∼150 000 natural products, ∼150 fluorophores, ∼1100 endogenous human metabolites (Recon2) and 1387 marketed drugs studied previously [25]. Molecules were extracted by the present authors [26] to a latent space of 100 dimensions using methods described in [27] and their vector values in the latent space used as the input to the UMAP algorithm.…”
Section: A Brief History Of Virtual Screening and The Multilayer Percmentioning
confidence: 99%
“…(B) UMAP [24] representation of the chemical space of ∼6 M 'druglike' molecules from ZINC. This is largely seen to contain the ∼150 000 natural products, ∼150 fluorophores, ∼1100 endogenous human metabolites (Recon2) and 1387 marketed drugs studied previously [25]. Molecules were extracted by the present authors [26] to a latent space of 100 dimensions using methods described in [27] and their vector values in the latent space used as the input to the UMAP algorithm.…”
Section: A Brief History Of Virtual Screening and The Multilayer Percmentioning
confidence: 99%
“…[34,79,80]). Indeed, many drugs show structural similarities with fluorophores [81]. Early evidence showed that fluorescent dyes such as rhodamine derivatives used in the study of drug efflux require mediated membrane transport influx in the first place [82], and the same is true for nucleic acid stains such as ethidium bromide [83,84].…”
Section: Role Of Fluorescent Stains In Understanding Microbial Physiomentioning
confidence: 99%
“…Thus, the purpose of the present article is to describe our own implementation of a simple VAE and its use in molecular similarity measurements as applied, in particular, to the set of drugs, metabolites and natural products that we have been using previously [ 25 , 99 , 100 , 101 , 102 , 103 , 104 ] as our benchmark for similarity metrics. A preprint was deposited at bioRxiv [ 105 ].…”
Section: Introductionmentioning
confidence: 99%